The Influence of Influencer Marketing, Fomo and Service Quality on Purchasing Decisions at Cafe Renjana Bengkulu City - Octarani, Elviana Dwi; Hidayati , Arifah; Noor Army, Muhammad (Journal of Management, Economic, and Accounting, 2025)
This study aims to determine the effect of variable X (Influencer Marketing, FOMO, and Service Quality) on variable Y (Purchase Decision) at Cafe Renjana, Bengkulu City. This study uses a quantitative method that is explanatory research to determine the effect between independent variables and dependent variables. The population in this study is not known for sure. Determination of the number of samples using the theory of Hair et al (2010) depends on the number of indicators multiplied by ten. The sample in the study was one hundred and fifty people. The data source in this study was taken from the results of the research questionnaire. The analysis used in this study to see whether or not there is an effect using the Hypothesis test and to see the magnitude of the effect using the correlation test. The results of this study are: a) there is an effect between Influencer Marketing (X1) on Purchase Decision (Y) with a very strong degree of relationship. b) there is an effect between FOMO (X1) on Purchase Decision (Y) with a very strong degree of relationship. c) there is an effect between Service Quality (X2) on Purchase Decision (Y) with a very strong degree of relationship. d) there is an influence of the Influencer Marketing Variables (X1), FOMO (X2) and Service Quality (X3) on Y (Purchase Decision) with a very strong degree of relationship.